The role of knowledge management in developing intellectual capital Case study of the University of Tamanrasset - Med Mounir kacemi (مجلة الاجتهاد للدراسات القانونية والاقتصادية)
This study aimed to know the attitudes of the respondents at the University of Tamanrasset, about the role of knowledge management in the development of intellectual capital. sample total.